2017
DOI: 10.1371/journal.pone.0169673
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Bone Turnover Markers after Risk-Reducing Salpingo-Oophorectomy in Women at Increased Risk for Breast and Ovarian Cancer

Abstract: BackgroundRisk-reducing salpingo-oophorectomy (RRSO) reduces ovarian cancer risk in BRCA1/2 mutation carriers. Premenopausal RRSO is hypothesized to increase fracture risk more than natural menopause. Elevated bone turnover markers (BTMs) might predict fracture risk. We investigated BTM levels after RRSO and aimed to identify clinical characteristics associated with elevated BTMs.MethodsOsteocalcin (OC), procollagen type I N-terminal peptide (PINP) and serum C-telopeptide of type I collagen (sCTx) were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Unlike our previous reports describing the occurrence of bone loss following development of colorectal tumours or after prolonged administration of chemotherapy, bone tissue is not generally investigated in the experimental models utilized for the study of HGS‐OCs. In the clinical setting, OC is not frequently associated with enhanced bone fractures per se or described as a risk factor for the development of osteoporosis, although elevated bone turnover markers were detected in women undergoing risk‐reducing salpingo‐oophorectomy to decrease the risk for breast cancer and OC . Surgery represents the preferred treatment for OC and frequently involves the removal of both ovaries as a part of treatment, eventually followed by radiation therapy, intraperitoneal chemotherapy with platinum and a taxane, or hormone replacement treatment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike our previous reports describing the occurrence of bone loss following development of colorectal tumours or after prolonged administration of chemotherapy, bone tissue is not generally investigated in the experimental models utilized for the study of HGS‐OCs. In the clinical setting, OC is not frequently associated with enhanced bone fractures per se or described as a risk factor for the development of osteoporosis, although elevated bone turnover markers were detected in women undergoing risk‐reducing salpingo‐oophorectomy to decrease the risk for breast cancer and OC . Surgery represents the preferred treatment for OC and frequently involves the removal of both ovaries as a part of treatment, eventually followed by radiation therapy, intraperitoneal chemotherapy with platinum and a taxane, or hormone replacement treatment .…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, OC is not frequently associated with enhanced bone fractures per se or described as a risk factor for the development of osteoporosis, although elevated bone turnover markers were detected in women undergoing risk-reducing salpingooophorectomy to decrease the risk for breast cancer and OC. 72,73 Surgery represents the preferred treatment for OC and frequently involves the removal of both ovaries as a part of treatment, eventually followed by radiation therapy, intraperitoneal chemotherapy with platinum and a taxane, or hormone replacement treatment. 74 Consistently, women treated for their gynaecologic cancers are often affected with hypogonadism, along with reduced BMD as a consequence of surgical or chemotherapy treatments.…”
Section: Es-2 Cells Cause Cachexia In Vivomentioning
confidence: 99%
“…Participants visited the outpatient clinic, filled out a questionnaire on socio-demographic characteristics, medical history, hormonal exposure [including use of systemic hormone replacement therapy (HRT)] and lifestyle, provided anthropometric measures and a blood sample, and had a bone mineral density measurement. Results on the association between RRSO and bone-related outcomes are available elsewhere [ 21 , 22 ]. For the current study, patients who reported CVD before RRSO (N = 2) or from whom a blood sample was not available for analyses (N = 3) were excluded, and 207 remained for analyses.…”
Section: Methodsmentioning
confidence: 99%
“…However, premenopausal RRSO leads to early surgical menopause which has detrimental long-term health sequelae (increased risk of coronary heart disease, osteoporosis, vasomotor symptoms, sexual dysfunction, neurocognitive decline) particularly in women unable to use hormone replacement therapy (HRT). [8][9][10][11][12][13] Widespread acceptance of a central role for the fallopian tube in the development of highgrade serous carcinoma (HGSC), the most common type of OC has led to early salpingectomy (ES) followed by delayed oophorectomy (DO) proposed as an attractive alternative two-step OC surgical prevention strategy in premenopausal women who have completed their family but decline/wish to delay RRSO. Epidemiological studies show 70% of occult lesions identified in high-risk women undergoing RRSO occur in the tube and that salpingectomy may reduce ovarian cancer risk in low-risk women by 42%-65%.…”
Section: Original Researchmentioning
confidence: 99%